Mistrust in the Neighbor: An Obstacle for the Communication Plans for Social Cohesion in Rural Sectors of Colombia (2018)
The development of public sector activities in Colombia, aimed at affecting the peasants' standard of living, is hampered by the lack of credibility of public entities and external staff. However, the lack of confidence in the neighbors' actions is specially surprising. Understanding the issue of distrust becomes a fundamental element in social cohesion processes in Colombia, given the current situation. This article analyzes the feeling of distrust among neighbors of a rural community in the irrigation district of Monquirá (Boyacá, Colombia), and intends to contribute elements for actions aimed at creating social cohesion programs, in scenarios in which the trust in neighborhood communities is sought. The investigation starts from the following question: what is the degree of trust in the members of the same community that assume leadership and representation roles in State entities? To find out, a non-probabilistic sample was carried out, in which an unstandardized instrument, based on the three levels of Kelman's social influence, was applied. The study allowed to understand the behavior of the users of the irrigation district. It was found that the individuals fear that the neighbors will not comply with their commitments, and a fragmentation of the social cohesion is evidenced due to the distrust in the actions of the other.